Two and Three Dimensional Image Registration Based on B-Spline Composition and Level Sets (Communications in Computational Physics, 2018)
A method for non-rigid image registration that is suitable for large deformationsis presented. Conventional registration methods embed the image in a B-splineobject, and the image is evolved by deforming the B-spline object. In this work, we representthe image using B-spline and deform the image using a composition approach.We also derive a computationally efficient algorithm for calculating the B-spline coefficientsand gradients of the image by adopting ideas from signal processing usingimage filters. We demonstrate the application of our method on several different typesof 2D and 3D images and compare it with existing methods.